Biomimetic nanostructures in ZnS and ZnSe provide broadband anti-reflectivity. (18th October 2017) - Chan, L; DeCuir, E A; Fu, R; Morse, D E; Gordon, M J
Abstract: Graded-index, moth eye-inspired anti-reflective features were fabricated in ZnS and ZnSe via nanosphere lithography using a Langmuir–Blodgett dip-coating method with plasma-based mask reduction and pattern transfer. Arrays of hexagonally close-packed conical frusta (top diameter = 300 nm, pitch = 690 nm, height = 2800 nm) were realized by isotropic etching (size-reduction) of the colloidal mask with CF4 /Ar, followed by pattern transfer into the substrate using CH4 /H2 plasma etching. Substantial increases in broadband transmission were achieved across the 2–20 μ m range, yielding 23% and 26% single-side transmission improvement, and 92% and 88% absolute double-side transmission for ZnS and ZnSe, respectively, in excellent agreement with finite difference time domain (FDTD) optical simulations. Experimental differences in direct versus total transmission, and the general fall off of transmission at short wavelengths, were attributed to diffuse forward scattering and diffractive effects, as predicted by far-field scattering patterns using FDTD. The fabrication method presented can be used to enhance efficiency for multiple IR applications by minimizing reflective losses, while offering the further advantages of scalability and low cost.